Post-traumatic Corneal Ocular Surface Squamous Neoplasia: A Case Report - Keerti Wali; Nikita Sankolli; Savitri Nerune (TNOA Journal of Ophthalmic Science and Research)
We report a rare presentation of limbus-sparing ocular surface squamous neoplasia (OSSN) over post-traumatic adherent leucoma. A 32-year-old healthy male presented with a pedunculated fleshy corneal mass overlying an adherent leucoma secondary to self-healed full-thickness corneal laceration, with an adjacent pinguecula separated by a clear normal limbus. AS-OCT confirmed the separation of corneal epithelial mass from underlying iris tissue by thinned scarred corneal stroma. An excisional biopsy with 2mm conjunctival margins and a limbal conjunctival autograft was performed. A feeder vessel was observed at the base of the corneal lesion. Histopathological evaluation showed moderately differentiated squamous cell carcinoma. Adjuvant Interferon alfa 2b chemotherapy for three months ensured complete clearance with no recurrence at follow-up. This case highlights the traumatic etiology of OSSN development without limbal involvement. Immediate corneal tear repair may have prevented its occurrence and the need for long-term chemotherapy.